Eksistensi Program Dakwah di Siaran Televisi pada Momen Ramadan 1445 H - Imansari, Nitra Galih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This research highlights the existence of da'wah programs on television stations, seeing that this media is now starting to be abandoned by many audiences. However, every time Ramadan comes, every television station competes to show its flagship programs. To see this phenomenon, it is necessary to observe the extent of the program's existence so that it remains consistent. This research aims to know the importance of the existence of da'wah programs on television stations during Ramadan. This research approach uses descriptive qualitative documents and observations. This research found strategies to ensure that the program continues to exist with existing competitors. Program creativity combines entertainment and education, creativity of program concepts, and creativity of program themes.